Achieving energy justice and common prosperity through green energy resources. (March 2023) - Sun, Yunpeng; Wang, Jin; Wang, Xiuhui; Wei, Xinyu
Abstract: Energy justice is one of the essential concepts which has an impact on social prosperity. This paper investigates the relationship between green energy justice and social prosperity by employing a panel data approach and annual data from 23 Chinese provinces from 2000 to 2021. The empirical findings confirmed that the price of energy (electricity) negatively affects energy justice. The difference in income level has a negative and significant coefficient. Social prosperity has a positive and meaningful effect on green social justice. In addition, in provinces with a high level of GDP, the quality of governance significantly affects the justice of green energy. Developing planning in each province, enhancing green financing markets, and establishing the China National Green Energy Justice Network (CNGEJN) are three significant practical policies recommended by this research. Highlights: Social prosperity has a positive impact on green social justice. Governance quality has an impact on green energy justice. Electricity price has a negative effect on energy justice.